Abundance of Colistin-Resistant, OXA-23- and ArmA-Producing Acinetobacter baumannii Belonging to International Clone 2 in Greece - Palmieri, Mattia; D’Andrea, Marco Maria; Pelegrin, Andreu Coello; Perrot, Nadine; Mirande, Caroline; Blanc, Bernadette; Legakis, Nicholas; Goossens, Herman; Rossolini, Gian Maria; van Belkum, Alex (Frontiers in Microbiology, 2020)
Carbapenem resistant Acinetobacter baumannii (CRAB) represents one of the most challenging pathogens in clinical settings. Colistin is routinely used for treatment of infections by this pathogen, but increasing colistin resistance has been reported. We obtained 122 CRAB isolates from nine Greek hospitals between 2015 and 2017, and those colistin resistant (ColR) (N=40, 32.8%) were whole genome sequenced, also by including two colistin susceptible (ColS) isolates for comparison. All ColR isolates were characterized by a previously described mutation, PmrBA226V, which was associated with low-level colistin resistance. Some isolates were characterized by additional mutations in PmrB (E140V or L178F) or PmrA (K172I or D10N), first described here, and higher colistin MICs, up to 64 mg/L. Mass spectrometry analysis of lipid A showed the presence of a phosphoethanolamine (pEtN) moiety on lipid A, likely resulting from the PmrA/B-induced pmrC overexpression. Interestingly, also the two ColS isolates had the same lipid A modification, suggesting that not all lipid A modifications lead to colistin resistance or that other factors could contribute to the resistance phenotype. Most of the isolates (N=37, 92.5%) belonged to the globally distributed international clone (IC) 2 and comprised four different sequence types (STs) as defined by using the Oxford scheme (ST 425, 208, 451 and 436). Three isolates belonged to IC1 and ST1567. All the genomes harbored an intrinsic blaOXA-51 group carbapenemase gene, where blaOXA-66 and blaOXA-69 were associated with IC2 and IC1, respectively. Carbapenem resistance was encoded by the most commonly reported acquired carbapenemase gene blaOXA-23, with ISAba1 located upstream of the gene and likely increasing its expression. The armA gene, associated with high-level resistance to aminoglycosides, was detected in 87.5 % of isolates. Collectively, these results revealed a convergent evolution of different clonal lineages towards the same colistin resistance mechanism, thus limiting the effective therapeutic options for the treatment of CRAB infections.